A PROSPECTIVE STUDY OF SAFETY AND EFFICACY OF ORAL ANALGESICS IN THE MANAGEMENT OF ACUTE MUSCULOSKELETAL PAIN - PRIYA, M. TEJASWI SAI; SONIA, S. SHARON; SAGI, PADMA SRAVANI (International Journal of Current Pharmaceutical Research, 2024)
Objective: Musculoskeletal pain is a significant health problem in adolescents and challenging condition for clinicians and physicians. Acute musculoskeletal pain is sudden and severe which lasts less than 12 w. This study was aimed to assess the efficacy safety of oral analgesics in the management of the condition. Methods: A Prospective study on oral analgesics prescribed routinely for this pain was conducted among 100 patients who attended OPD, at Area Hospital, Dharmavaram. 25 patients were included in each group; group a were given tramadol 100 mgOD, group B-paracetmol 500 mgBD, Group C-ibuprofen 200 mgBD and group D-dicolfenac 50 mgBD. The severity of pain assessed by Visual Analogue Scale (VAS) and Verbal Rating Scale (VRS). The data was analysed by using SPSS-21version. Results: Number of subjects included in the analysis 100 who were divided equally into 4 groups. The improvement in pain relief as follows-Group a given tramadol 100 mg showed pain relief of 80%VAS and 84%VRS. Group b given paracetmol 500 mgBD-40% by VAS and VRS. Group c given ibuprofen 200 mgBD showed 60% by VAS and 68% by VRS. GROUP D given diclofenac 50 mgBD showed better improvement of pain relief i. e 88% by VAS and 96% by VRS, yet the p-value is 0.001, showing difference statistically significant. Conclusion: Among all 4 groups, Tramadol and Diclofenac showed better response (80% and 84%;88 and 96% respectively). Diclofenac is non-opioid. Hence, considering safety and improvement in pain relief in acute musculoskeletal Pain, Oral Diclofenac is preferred analgesic of choice over oral tramadol, an opioid with an adverse drug reaction profile that includes rising BP, causing seizure and addiction liability.